Effects of Malaysian employee stock option scheme on stock liquidity, productivity, and earnings management of listed firms - Katan, Maheran (2012)
This study investigates whether Malaysian Employee Stock Option Scheme (Esos)is related to stock liquidity and the mechanisms through which the relationship is established. In particular, it examines the effect of Esos on stock liquidity and which of the two conflicting effect of Esos; productivity effect or earnings management effect is responsible for the potential effect of Esos on stock liquidity. To assess stock liquidity of Esos adopting firms, three measures of stock liquidity are employed. They are relative bid-ask spread, turnover ratio and liquidity ratio. The effect of Esos on productivity is measured using Data Envelopment Analysis and to evaluate the level of earnings management practices, this study employs two earnings management models; Modified Jones Model by Dechow, Sloan & Sweeney (1995) and performance-matched discretionary accruals model by Kothari, Leone & Wasley (2005). The empirical results indicate that Esos adoption has statistically significant effect on the firm’s stock liquidity. In terms of the productivity effect of Esos adoption,this study finds no evidence of statistically significant impact of Esos on firm productivity. With regards to the effect of Esos on earnings management practices,this study documents a statistically significant link between Esos and earnings management. A multivariate analysis is conducted to test the association between Esos and earnings management while controlling for other factors proposed in the literature as motivation for earnings management. The results of the multivariate analysis demonstrate a positive and highly significant relationship between Esos and earnings management. To further verify whether the increase in stock liquidity is driven by productivity enhancement or earnings manipulation, the relationship between stock liquidity, productivity and earnings management is tested while controlling for other determinants of stock liquidity. The result of the multivariate analysis shows insignificant relationship between stock liquidity and productivity but significant relationship between stock liquidity and earnings management. Overall, this study finds that the significant increased in stock liquidity after implementation of Esos is supported by manipulated earnings rather than the fundamental increase in productivity. It can be concluded that these results are consistent with rent-seeking theory which states that instead of drawing the interest of stockholders and employees together through productivity enhancement, Esos induces opportunistic earnings management practices. The existing Esos guideline has to be improved to ensure that Esos motivates employees to increase their productive efforts and at the same time encourages and fosters managerial virtues.